Analysis Disciplinated Docents of the Faculty of Economy and Business Islam UIN Raden Mas Said Surakarta - Dewi Avifa Ariasti Ariasti; Safa Putri Indriyana; Salsa Bella Putri (LPPM STIAB Jinarakkhita Lampung, 2023)
The purpose of this research is to find out and analyze the lecturer discipline at the Faculty of Economics and Business Islam UIN Raden Mas Said Surakarta. Discipline is the process or result of directing or controlling a desire, urge, or interest toward an ideal or to produce more effective and reliable behavior. The research approach used in this study is a qualitative approach with a type of descriptive method. Sampling technique using purposive sampling. Based on the analysis results of the informants, the lecturer discipline of the Faculty of Economics and Islamic Business UIN Raden Mas was excellent. The results of this study explained that employees obey the rules set by the organization not because they fear punishment but because they understand and support them. To get the accreditation of a good agency, the discipline and responsibility of its employees will be necessary. With time management and cultivation, discipline will encourage officers to act and carry out all activities according to the rules that have been established.